The professional literary agent in Britain, 1880-1920 - Gillies, Mary Ann, 1959- (Studies in book and print culture., 2007)
"Breaking new ground in the study of British literary culture during an important, transitional period, this new work by Mary Ann Gillies focuses on the professional literary agent whose emergence in Britain around 1880 coincided with and accelerated the transformation of both publishing and authorship." "Like other recent studies in book and print culture, The Professional Literary Agent in Britain, 1880-1920 starts from the central premise that the business of authorship is inextricably linked with the aesthetics of literary praxis. Rather than provide a broad overview of the period, however, Gillies focuses on a specific figure, the professional literary agent. She then traces the influence of two prominent agents - A.P. Watt (generally acknowledged as the first professional literary agent) and J.B. Pinker (the leading figure in the second wave of agents) - focusing on their respective relationships with two key clients. The case studies not only provide insight into the business dynamics of the literary world at this time, but also illustrate the shifting definition of literature itself during the period."--Jacket